PERBANDINGAN KADAR ETANOL HASIL FERMENTASI SUBSTRAT DAMI NANGKA (Artocarpus heteropyllus Lamk.) DENGAN MENGGUNAKAN KULTUR MURNI Trichoderma viride DAN Saccharomyces cerevisiae - Mardiyah, Siti; Widyaningrum, Trianik (BIO-SITE |BIOLOGI Sains Terapan, 2015)
Jackfruitâs dami (Artocarpus heterophyllus Lamk.) is a material that can be used as substrates in the manufacture of ethanol. The process of making ethanol fermentation is done by using a pure culture of Trichoderma viride and Saccharomyces cerevisiae. This study aims to determine the effect of treatment of a pure culture fermentation of the fungi Trichoderma viride on jackfruitâs dami (Artocarpus heterophyllus Lamk.) Against ethanol and compare the levels of ethanol fermented jackfruitâs dami substrate using Trichoderma viride pure culture and pure cultures of Saccharomyces cerevisiae. This study uses a completely randomized design (CRD) with factorial pattern using two factors: 1) Trichoderma viride and Saccharomyces cerevisiae, 2) Saccharomyces cerevisiae without Trichoderma viride. Furthermore, the data were analyzed using analysis of variance (ANOVA) and test T. If there is a significant difference, then continued with LSD test level of 5%. The results showed that higher levels of ethanol contained in the treatment without the use of Trichoderma viride and using Saccharomyces cerevisiae with a dose of 108 Cfu/ml which is 0.7851%, while the lowest levels of ethanol produced in the treatment with Trichoderma viride using doses of 5 ml and a dose of Saccharomyces cerevisiae 108 Cfu/ml is 0.1906 %. Â Keywords : Fermentation, jackfruitâs dami, Trichoderma viride, Saccharomyces cerevisiae, Concentration of ethanol.